Effect of Combination of Porang Tuber Glucomannan (Amorphophallus muelleri blume) with Moringa Leaf Extract on Red Blood Cell Count in Obese White Rats (Rattus norvegicus) Strain Wistar - Rotama, Sigit; Wicaksono, Muhammad Galih; Tias, Eriza Putri Ayu Ning; Setyaningsih, Endang (Universitas Muhammadiyah Surakarta, 2024)
As times have changed, so have lifestyles that have adverse health effects, including obesity. Obesity is known to potentially affect the number of red blood cells in the body. Obesity can cause iron deficiency in children and adolescents, which can develop into anemia. The aim of this study was to determine the effect of obesity on the number of red blood cells and to investigate the effect of a combination of glucomannan and moringa leaf extract on the number of red blood cells in obese white Wistar strain rats. The research method used was a true experimental design in the form of a post-test only control group with three treatment groups: the control group, treatment group P1 and treatment group P2. The results of the calculations showed differences in the number of red blood cells in each treatment. In the control treatment, there were 7.16/L. In the P1 treatment, the RBCs were 3.24 million/L. In contrast, the P2 treatment yielded a result of 5.02 million red blood cells per liter. It can be concluded that the combination of Porang Tuber Glucomannan with Moringa Leaf Extract can reduce body weight and normalize the number of red blood cells.